Pengaruh Akupresur Titik BL22 dan BL23 pada Nyeri Pasca Pemasangan Kontrasepsi KB IUD di Puskesmas Bululawang - Tiya Damaiyanti, Anis; Prisusanti, Retno Dewi; Retnaningsih, Reny (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Pain following the insertion of an intrauterine contraceptive device (Intra Uterine Device/IUD) is a common complaint among family planning acceptors and may affect comfort as well as the continuation of long-term contraceptive use. One non-pharmacological method that has the potential to reduce pain is acupressure therapy. This study aimed to determine the effect of acupressure at points BL22 and BL23 on reducing pain levels after IUD insertion at Bululawang Community Health Center. This research employed a quasi-experimental design with a non-equivalent control group pretest-posttest approach. The sample consisted of 32 respondents, divided into an intervention group and a control group, each comprising 16 respondents. Pain levels were measured using the Visual Analogue Scale (VAS). The results showed that before the intervention, all respondents experienced severe pain with a mean value of 3.00. After the intervention, the intervention group experienced a decrease in pain to a mean of 0.31, while the control group decreased to a mean of 0.56. The Wilcoxon test results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of acupressure on reducing pain levels after IUD insertion. In conclusion, acupressure at points BL22 and BL23 is effective in reducing pain after IUD insertion and can be used as a complementary therapy in midwifery services at primary healthcare facilities.